Asterless is a scaffold for the onset of centriole assembly. - Dzhindzhev, N.S.; Yu, Q.D.; Weiskopf, K.; Tzolovsky, G.; Cunha-Ferreira, I.; Riparbelli, M.; Rodrigues-Martins, A.; Bettencourt-Dias, M.; Callaini, G.; Glover, D.M. (Nature, 2010)
Centrioles are found in the centrosome core and, as basal bodies, at the base of cilia and flagella. Centriole assembly and duplication is controlled by Polo-like-kinase 4 (Plk4): these processes fail if Plk4 is downregulated and are promoted by Plk4 overexpression. Here we show that the centriolar protein Asterless (Asl; human orthologue CEP152) provides a conserved molecular platform, the amino terminus of which interacts with the cryptic Polo box of Plk4 whereas the carboxy terminus interacts with the centriolar protein Sas-4 (CPAP in humans). Drosophila Asl and human CEP152 are required for the centrosomal loading of Plk4 in Drosophila and CPAP in human cells, respectively. Depletion of Asl or CEP152 caused failure of centrosome duplication; their overexpression led to de novo centriole formation in Drosophila eggs, duplication of free centrosomes in Drosophila embryos, and centrosome amplification in cultured Drosophila and human cells. Overexpression of a Plk4-binding-deficient mutant of Asl prevented centriole duplication in cultured cells and embryos. However, this mutant protein was able to promote microtubule organizing centre (MTOC) formation in both embryos and oocytes. Such MTOCs had pericentriolar material and the centriolar protein Sas-4, but no centrioles at their core. Formation of such acentriolar MTOCs could be phenocopied by overexpression of Sas-4 in oocytes or embryos. Our findings identify independent functions for Asl as a scaffold for Plk4 and Sas-4 that facilitates self-assembly and duplication of the centriole and organization of pericentriolar material.